Stressor 2019: Zooplankton abundance, biovolume and size structure in the northern Norwegian Sea - Basedow, Sünnje Linnéa (DataverseNO, 2021)
Data on zooplankton abundance and biovolume are presented, in concert with data on the biophysical environment, from 17 transects (ca. 50-100 km long) crossing the shelf break off the Lofoten-Vesterålen islands during a research cruise with R/V Helmer Hanssen 27 April to 12 May 2019. The data were collected along vertical profiles from surface to 500-600 m depth by a free-fall Moving Vessel Profiler (MVP) equipped with Laser Optical Plankton Counter, (LOPC), Conductivity-Temperature-Depth (CTD) sensor and Fluorescence sensor (F). Position data were provided by the ships' GPS. Based on the analysis and calibration of these instruments, we created a data set with high spatial resolution, containing position (latitude, longitude, depth), environment (temperature, salinity, chlorophyll a), as well as zooplankton abundance and biovolume tabulated in 49 size classes (0.1-3 mm). A detailed description is provided in the README file.